Analysis of Employee Performance Quality Through The Use Of Online Attendance Attendance (Application) at Dinas Ketahanan Pangan Dan Pertanian Pesisir Barat - Mieke Rahayu; M Ilham Arridho Sani; Afra Raspita (Prosiding International conference on Information Technology and Business (ICITB), 2022)
The use of online attendance is the useof technology to support effectiveness in recording attendance within agencies. Many problems arise regarding absenteeism in agencies, namely the inevitable manipulation. Therefore, researchers want to examine the quality of employee performance in the west coast food security and agriculture service using online attendance. This study aims to find out how effective the use of online attendance is on the quality of performance. The number of samples taken was 100 respondents with purposive sampling. Data analysis in this study used the Structural Equation Model (SEM). From the results of data processing, the R square result of 0.939 is obtained, which means that variable X has a significant effect on variable Y through the intervening variable Z. Keywords—quality performance, finger print, discipline performance